Mendayagunakan Sumber-Sumber Pendidikan Untuk Meningkatkan Kemampuan Belajar - Maisya Nandia (Jurnal Transformasi Bisnis Digital, 2024)
Humans need education in their lives. In reality, education has been able to lead humans towards a more civilized life. To advance the nation's intelligence, adequate education is needed for the entire community. Of course, the expected education cannot immediately be implemented well. Many factors are needed to make this happen, including educational factors, student factors, environmental factors, infrastructure.